2015
DOI: 10.3389/feart.2015.00032
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of onshore digital elevation models for modeling tsunami inundation zones

Abstract: A sensitivity study is undertaken to assess the utility of different onshore digital elevation models (DEMs) for simulating the extent of tsunami inundation using case studies from two locations in Indonesia. We compare airborne IFSAR, ASTER, and SRTM against high resolution LiDAR and stereo-camera data in locations with different coastal morphologies. Tsunami inundation extents modeled with airborne IFSAR DEMs are comparable with those modeled with the higher resolution datasets and are also consistent with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 37 publications
(71 reference statements)
3
60
0
Order By: Relevance
“…In this regard, Gallegos et al [67] suggested that a horizontal resolution of 5 m may be required for detailed evaluation of risk assessment, so SRTM DEM may not have sufficient resolution to simulate flood inundation with confidence. Similar observations have been made in other studies [3,7,63]. However, the 50 m DEM, which is an OS derivative from 10 m contours using photogrammetric techniques that are updated annually using other high-resolution terrain datasets, provides much better estimates of the total flooded areas despite the low horizontal resolution [34].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this regard, Gallegos et al [67] suggested that a horizontal resolution of 5 m may be required for detailed evaluation of risk assessment, so SRTM DEM may not have sufficient resolution to simulate flood inundation with confidence. Similar observations have been made in other studies [3,7,63]. However, the 50 m DEM, which is an OS derivative from 10 m contours using photogrammetric techniques that are updated annually using other high-resolution terrain datasets, provides much better estimates of the total flooded areas despite the low horizontal resolution [34].…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the DTM contains significantly lower elevation values, which results in a greater flooded area than a DSM. Griffin et al [63] argued that the best approach for modelling flood inundation is to use a DTM together with an appropriate surface roughness condition, but their studies deal with tsunami inundation where the water flow has the force to destroy buildings. For SLR flooding, the ideal DEM may lie between a DSM and a DTM, because some structures may resist flow, while others allow water to flow through them and may even collapse with prolonged flooding.…”
Section: Discussionmentioning
confidence: 99%
“…In open terrain, the SRTM elevation will represent the ground elevation, but in vegetated or urban areas the ground-elevation might be overestimated. According to Gesch (2009), this mix of ground elevation and non-bare ground elevation in SRTM data could be a source of error in inundation mapping in vegetated and urban areas (Baugh et al, 2013;Lewis et al, 2013;Griffin et al, 2015). The second data set used is the (2) Light detection and ranging (LiDAR) digital elevation model (datum wgs84) with a spatial resolution of 5 m and a vertical accuracy of (±)20 cm which was provided by the Emilia-Romagna region.…”
Section: Exposure Datamentioning
confidence: 99%
“…For instance, the deterministic approach is more communicable to the authorities for developing post-disaster recovery and mitigation plans (McGuire, 2001). However, implementation of deterministic scenarios may oversimplify the tsunami hazards and risks, leading to imprecise mitigation plans (Griffin et al, 2015;Mueller et al, 2015). In contrast, the probabilistic approach requires the proper consideration of regional earthquake characteristics, including uncertainties in the earthquake rupture size, its focal mechanism, and the depth and spatial heterogeneity of the earthquake slip.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Muhammad et al (2016) have evaluated the tsunami potential in Padang by developing the stochastic tsunami simulation method, allowing us to generate numerous scenarios of stochastic tsunami hazard. However, that work was limited to evaluating the tsunami hazards offshore and near the coast only because of the gross bias of the elevation model in Padang (Griffin et al, 2015) and, therefore, was not suitable to carry out rigorous assessment of tsunami mitigation systems. The gross bias of the elevation model in Padang is due to the use of global digital elevation model (DEM; i.e., GDEM2) as the elevation data for the stochastic tsunami simulation.…”
Section: Introductionmentioning
confidence: 99%